PROFIT AND LOSS OF INCREASE IN HAJJ COSTS FOR PROSPECTIVE INDONESIAN HAJJ PILGRIMS - R.A. Indrawati; Akhmad Riduan; Syamsu Rijal; Roikhan Mochamad Aziz; Muhammadong (Adisam Publisher, 2024)
The increase in Hajj costs for Indonesian Hajj pilgrims has generated various kinds of controversy. One side believes that this policy must be implemented because the exchange rate is unstable which causes accommodation costs to rise, transportation costs to rise, and other service costs to rise. However, on the other hand, they believe that this policy was implemented in a hurry and was not socialized first, which could cause the congregation to default and fail to leave, forcing them to leave in debt, and denying the congregation other basic needs, thus reducing their purchasing power. This research is qualitative research with a descriptive approach. The data used in this research is secondary data that researchers obtained from websites, scientific articles, books and other reliable sources. The data was analyzed using the stages of data collection, data selection, data reduction, data analysis using the SWOT method, and drawing conclusions.